Silencing NRF2 enhances arsenic trioxide-induced ferroptosis in hepatocellular carcinoma cells - Mi Huang; Duanzhuo Li; Zhengzhen Xia; Shengjie Liao; Wenxia Si; Chao Yuan; Yanli Liao; Weibin Wu; Minshu Jiang; Xin Yu; Yi Quan (PLoS ONE, 2025)
Objective Hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths worldwide, with high mortality rates partially due to limited therapeutic options and drug resistance. Arsenic trioxide (ATO), a compound clinically proven for acute promyelocytic leukemia (APL), has garnered attention for its emerging efficacy in solid tumors, including HCC. However, the molecular mechanisms driving ATO’s antitumor activity in HCC remain incompletely understood. In this study, we aimed to elucidate the ferroptosis-dependent effects of ATO on HCC and and propose a potential therapeutic strategy. Methods The response of HCC cells to ATO was evaluated using cell viability, wound healing, colony formation, Transwell migration assays, and cell cycle analysis. ATO-induced ferroptosis was assessed by measuring lipid peroxidation (via C11-BODIPY staining), intracellular iron levels, and malondialdehyde (MDA) production. Western blotting was performed to quantify protein levels of NRF2, HO-1, SLC7A11, and GPX4; immunofluorescence staining was employed to determine NRF2 subcellular localization. Results ATO exhibited significant cytotoxicity and inhibited the progression of HCC cells. Treatment with ATO resulted in a notable increase in lipid ROS and MDA levels, which were subsequently reversed by the ferroptosis inhibitors Fer-1 and DFO. Mechanistically, ATO induced ferroptosis by inhibiting GPX4. Furthermore, NRF2 and its downstream targets, HO-1 and SLC7A11, were upregulated during ferroptosis. NRF2 knockdown enhanced lipid peroxidation and ATO-induced cell death. Conclusions ATO significantly promoted ferroptosis in HCC cells, and NRF2 knockdown enhanced the cytotoxic effects of ATO.